JURISPRUDENTIAL AND LEGAL ADAPTATION OF PLASTIC SURGERY - Jamal Fateh Ali (Scholars Digest Publishing, 2023)
This research aims to clarify the jurisprudential and legal ruling on plastic surgery, a jurisprudential legal study, and follows the importance of research by highlighting the legal rooting. And adjusting the organs of the body from enlarging and minimizing to resemble what is desirable from celebrities, and it is of two types: a permissible type, and a prohibited type, and it included a number of conclusions that I was able to reach after studying the subject and knowing it in all its aspects - within the limits of the researcher's knowledge and the breadth of the research papers raised.
Keywords: jurisprudence, legal, operations, plastic surgery, treatment.